Outcomes associated with the use of a revised risk assessment strategy to predict antibiotic resistance in community-onset pneumonia: a stewardship perspective. (11th June 2018) - Farkas, Andras; Sassine, Joseph; Mathew, Joseph P; Stavropoulos, Christine; Stern, Ron; Mckinley, George
Abstract: Objectives: There is growing evidence that patients with community-onset pneumonia and recent healthcare exposure are not at equally high risk of infection with MDR organisms. An individualized approach is necessary with regard to risk assessment and choice of antibiotics. Methods: We reviewed the records of 102 patients admitted for community-onset pneumonia, before and after the implementation of a revised risk assessment programme for MDR organisms using the drug resistance in pneumonia (DRIP) score. The primary aim of the study was to identify the effects of this intervention on antibiotic days of therapy (DOT), and secondary outcomes included all-cause readmissions and time to clinical improvement. Statistical analysis was performed using generalized linear regression and Cox hazards models. Results: Implementation of the programme resulted in a decrease in anti-MRSA (−1.44 DOT, P = 0.007) and anti-pseudomonal (−2.03 DOT, P < 0.001) antibiotic utilization, but was not associated with a significant difference in the odds of readmissions (OR 0.64, 95% CI 0.16–2.57) or in time to clinical improvement (HR 1.19, 95% CI 0.62–2.21). Conclusions: An individualized MDR organism risk assessment strategy using a clinical prediction score for community-onset pneumonia can decrease the utilization of broad-spectrum antibiotics without an increase in adverse outcomes.